SIKAP BELA NEGARA SEBAGAI KONTROL DIRI DALAM MEMINIMALISIR PERILAKU KECURANGAN DIPANDANG DARI PERSPEKTIF FRAUD DIAMOND - Marisa, Ani; Susilowati, Endah (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
This research aim to test and empirically demonstrate how pressure, opportunity, rationalization, and capacity can influence academic fraud behaviour and how national defense attitudes play a role in moderating such influence. This research is a quantitative study using up to 94 students from S1 Accounting student UPN “Veteran” East Java as samples. The research used SEM PLS with WarpPLS 7.0 software for data analysis. The finding of this research may be used as a resource for universities related to fraud in the university environment, specially in S1 Accounting students and can provide an overview of fraud related to occurring, so that the universities can take determined further action to deal with such matters. Research findings demonstrate that pressure and rationalization have a significant influence on fraud behavior and national defense attitudes can moderate the influence of opportunity against fraud behavior. Opportunity and capability have no significant influence on fraud behavior and national defense attitudes do not moderate the influence of pressure, racinoalization, and capability against fraud behavior.